(3fePLI GdbQGQGJ GdEOGQjI(B"(3GdLRA GdKGfj(B"s - (3Ydj MSjf(B, (3Ydjs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI(B,s, 1999)
(3feGPL Gdfbd GdeMhQg,GJNGP GdbQGQ GdGeKd HGSJNOGe feGPL GdHQeLI GddGNWjI,GdHQeLI GdOjfGejcjI,s
(3HHdjhZQGajG,GdeQGLY(B:(3U(B.245-247s
Keywords: (3GJNGP GdbQGQGJs